(3cfR GdCSQGQ aj GdUdGI Ydi GdfHj GdeNJGQ Udi Gddg Ydjg hSdes - (3YHO Gddg Hf eMeO GdNjGW, CHh eMeO, GdTgjQ HGdgGQhTj,J (B1175 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGJM cfhR GdCSQGQ GdChdjGFg GdUGdMjf heGfM aJhMGJ GdESJHUGQ def JbQH Edjg HGdUdGI Ydi SjO GdeQSdjf s
(3BNQgG (B:s
(3Gddge eZaQJc ChSY ef PfhHi hQMeJc CQLi , YfOi ef Mdei KdGKkG hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf cedJ gPg GdUdhGJ GdeHGQcI HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B130 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B118s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(1216 (3O(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs